FRA1 (FOSL1) suppresses neoplastic transformation and modulates radiation responses via transcriptional control of mitogenic and stress-responsive networks - Al-Khayyat, Wuroud; Laframboise, Taylor; Dougherty, Jessica; Mendonca, Marc S.; Boreham, Douglas R.; Tai, T. C.; Thome, Christopher; Tharmalingam, Sujeenthar (Frontiers in Cell and Developmental Biology, 2025)
PurposeFOS-like antigen 1 (FRA1), encoded by FOSL1, is an inducible subunit of the AP-1 transcription factor complex and regulates gene expression in response to proliferative and environmental cues. Although FRA1 has been linked to cancer progression, its role in early transformation and radiation responses remains unclear.MethodsCRISPR-engineered human CGL1 cells—a hybrid of HeLa and normal fibroblasts—were used to evaluate the impact of FRA1 overexpression and knockout on neoplastic transformation. Transformation frequency, clonogenic survival, DNA damage recognition and repair, and cell cycle distribution were assessed following irradiation. Transcriptomic profiling was performed under baseline and serum-stimulated conditions.ResultsFRA1 loss markedly increased both spontaneous and radiation-induced transformation frequency, while overexpression suppressed transformation under both conditions. FRA1-deficient cells were sensitized to radiation-induced cell killing, despite intact DNA damage recognition and repair. In contrast, FRA1 overexpression promoted G2/M accumulation post-irradiation, suggesting enhanced checkpoint activation. Transcriptomic profiling revealed that FRA1 remodels AP-1 complex composition and functions as a transcriptional repressor of mitogen- and stress-responsive genes. FRA1-mediated repression was observed across gene networks involved in extracellular matrix remodeling, hypoxia signaling, inflammation, and proliferation, under both baseline and serum-stimulated conditions.ConclusionThese findings establish FRA1 as a key modulator of neoplastic transformation and radiation response, acting primarily through transcriptional repression of pro-tumorigenic signaling pathways.